2021
DOI: 10.3846/jcem.2021.15602
|View full text |Cite
|
Sign up to set email alerts
|

A Bim-Based Identification and Classification Method of Environmental Risks in the Design of Beijing Subway

Abstract: The subway project safety risk management in China covers design and construction stages. The traditional method for identifying construction safety risks at the design stage requires that engineers work backward, and it relies on engineers having an accurate understanding of complex engineering information, spatial relationships, and rich experience. This paper proposes a Building Information Modeling (BIM) based automatic identification and classification framework for environmental risks at the subway desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In order to reduce communication between project participants, (S. Zhang et al, 2017) [30] suggested the use of a BIM platform on which they could collaborate and manage the project. [14] integrates BIM platform technology with IoT technology to provide online, real-time exchange of information and personalization of products for assembled buildings. Nevertheless, few studies have incorporated BIM platforms with knowledge mapping technology and risk analysis models for dynamic and real-time intelligent risk management.…”
Section: A Risk Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to reduce communication between project participants, (S. Zhang et al, 2017) [30] suggested the use of a BIM platform on which they could collaborate and manage the project. [14] integrates BIM platform technology with IoT technology to provide online, real-time exchange of information and personalization of products for assembled buildings. Nevertheless, few studies have incorporated BIM platforms with knowledge mapping technology and risk analysis models for dynamic and real-time intelligent risk management.…”
Section: A Risk Managementmentioning
confidence: 99%
“…This cluster addressed the use of BIM in risk management. Accordingly, [79] designed an automatic identification and classification of environmental risks within a design phase BIM system, integrated risk management with an integrated BIM platform, and validated the risk management platform with the help of a specific project. An approach based on BIM that would identify environmental risks automatically and would facilitate the transfer of information regarding risk during construction in addition to increasing the efficiency of safety risk-specific design.…”
Section: C1 Abstract Co-vision Network Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Qazi et al (2020) said that interdependency modelling of uncertainty had been discussed using different qualitative and quantitative techniques. These models were based on the interpretive ranking process and system dynamics (Mhatre et al, 2017), Artifitial Intelligence (AI) (Afzal et al, 2021), fuzzy system (Valipour et al, 2015), meta-network analysis (Wang et al, 2021), Building Information Modelling (BIM) (Zhou et al, 2021) and multi-criteria decision-making model (Albogamy and Dawood, 2015;Burcar Dunovic et al, 2016). All these models were used to forecast the influence of uncertainties on project objectives.…”
Section: Criteria In the Tools And Techniques Componentmentioning
confidence: 99%
“…, 2015), meta-network analysis (Wang et al. , 2021), Building Information Modelling (BIM) (Zhou et al. , 2021) and multi-criteria decision-making model (Albogamy and Dawood, 2015; Burcar Dunovic et al.…”
Section: Theory About Uncertainty Management In the Design Phasementioning
confidence: 99%